A new species of Conchocarpus and first record of Euxylophora (Galipeinae, Zanthoxyloideae, Rutaceae) from Colombia - Londoño-Echeverri, Yeison; Trujillo-López, Ana María; Pérez-Zabala, Jorge Andrés (Phytotaxa, 2023)
Conchocarpus cardenasii, a new species from the Pacific biogeographical region in Colombia and named honors to the Colombian botanist Dairon Cárdenas (1957–2022), is described and illustrated with notes about its geographical distribution, phenology, conservation status, taxonomic affinities, and the morphology of its stamens. The basally sterile anthers it is the most distinctive feature, which is hitherto only reported for C. guyanensis, which however, can be easily differentiable by its corymbiform thyrses. This feature helps to recognize C. cardenasii from other morphologically resembling species such as C. grandis and C. jirajaranus, in addition to differences in leaves and fruits. Furthermore, the first record of Euxylophora paraensis for the Colombian Amazon is here presented, based on a specimen collected in 1951 by R. E. Schultes and I. Cabrera on the Apaporis River basin.